Expression of Viral DNA in Adenovirus Type 12-Transformed Cells, in Tumor Cells, and in Revertants - Schirm, Sabine (1981)
The expression as cytoplasmic RNA of integrated human adenovirus type 12 (Ad12) DNA in transformed and tumor cell lines and in revertants was investigated. The transformed and tumor cells contained multiple copies of the viral genome, 3 to 22 copies per cell in different cell lines. The integrated Ad12 DNA molecules persisted intact or nearly intact and in most cases colinear with the virion DNA. In the revertant cell lines, which were derived from cell line T637 (22 copies of Ad12 DNA per cell), all of the Ad12 DNA molecules were lost (line F10) or only one copy and a fraction of a second copy persisted (line TR12). The size classes and map locations of Ad12-specific cytoplasmic RNAs in three Ad12-transformed hamster cell lines (T637, HA12/7, and A2497-3), in two revertant lines (F10 and TR12), in one Ad12-induced hamster (CLAC3), and in one rat brain tumor line (RBT12/3) were determined. Cytoplasmic RNA from uninfected B3 hamster cells and from human KB cells productively infected with Ad12 served as controls. In the latter control experiments, the RNA was isolated early or late postinfection. With respect to the amounts of Ad12-specific RNAs detected in cytoplasmic RNA from various Ad12-transformed or Ad12-induced tumor cell lines, we could not establish any correlations to the number of Ad12 genome copies integrated into the cellular DNAs. Thus, the expression of the integrated viral genomes in these lines was regulated by mechanisms more complicated than simple gene dosage effects. Using cloned fragments of Ad12 DNA as hybridization probes, we analyzed the cytoplasmic RNAs from the cell lines mentioned by electrophoresis on agarose gels, blotting, and DNA-RNA hybridization. For each transformed and tumor cell line, except for the revertants, several size classes of Ad12-specific cytoplasmic RNA were detected for the early E1, E2, and E4 regions of Ad12 DNA. Some of these size classes were similar but not identical to those observed in cytoplasmic RNA isolated early from human KB cells productively infected with Ad12. Only cell lines A2497-3, T637, and RBT12/3 contained several size classes of cytoplasmic RNA homologous to the E3 region of Ad12 DNA. Weak homologies to the E1 region of Ad12 DNA were also detected in the revertant lines F10 and TR12. Late regions of Ad12 DNA were expressed as cytoplasmic RNA in cell lines CLAC3 and RBT12/3. Weak homologies were detected between certain segments of the Ad12 genome (the EcoRI-B, -C, and -D fragments) and the cytoplasmic RNA from uninfected hamster cells. These homologies had no apparent counterpart at the level of DNA, perhaps because these homologies could be detected only due to an overrepresentation of RNA sequences. In preliminary experiments, we failed to detect the expression as cytoplasmic RNA of the so-called virus-associated RNA in transformed and tumor cell lines. Virus-associated RNA represents a population of low-molecular-weight RNAs that map at around 30 fractional length units on the viral genome.